Além do dinheiro e dos demônios: o neopentecostalismo no Brasil e na Holanda - Medeiros, Rangel de Oliveira (2011)
The aim of this thesis is to analyze the Pentecostal discourse focusing primarily on various levels of discourse production of the Universal Church of the Kingdom of God (UCKG) and the International Church of the Grace of God (ICGG) in order to answer the following question: Is the structuring of these churches predominantly built on the theology of prosperity or on a more varied a range of discursive elements? Based on the hypothesis that these churches try to offer a full experience of life and religion, in opposition to the idea that has been spread by many non-academic commentators and academic works that these churches are only ―supermarket of faith‖, where the ―customer‖ ―buys‖ religious products that he will use in his worldly life and soon goes away, eventually to become ―customer of another supermarket‖. To this end we analyzed two different national contexts. Church activities were followed in Brazil, mainly in Florianopolis, and the Netherlands, especially in the capital Amsterdam. This work also has the characteristics of case study and comparative study. Information obtained during fieldwork in Brazil brought elements for analyzing the behavior of the church and its parishioners in a very different national context, thus enabling us to see what remains and what changes in the discourse of the church and the attitudes of the followers in the new context.